METHODOLOGY FOR APPLICATION OF THE SYSTEM APPROACH IN DESIGN AND CONSTRUCTION OF A LOGISTICS CENTER: METHODOLOGY FOR APPLICATION OF THE SYSTEM APPROACH IN DESIGN AND CONSTRUCTION OF A LOGISTICS CENTER - Peeva, Svetla (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The object of consideration of the present development are the elements clarifying the order in the system, which contribute to the more accurate construction of a system approach. The step-by-step presentation of the steps in the creation of a new logistics center aims to facilitate the logistics activities in the design and construction of large logistics structures.